Robert Nye’s Falstaff: A Remarkable Case of Creative Reception - Klein, Holger (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2012)
Among fictitious autobiographies as well as among historical novels, Robert Nye’s Falstaff (1976) is a special case in that it is not the autobiography of a historical personage, but of a dramatic character —who happens to be one of the most famous in Shakespeare, indeed in world drama, to be dictated by Falstaff to various amanuenses. After briefly discussing the sub-genre of fictitious autobiography, this paper will analyze the varied use of intertextuality, the tensions fabricated between the autobiographer and his helpers, and the critical thoughts and tendencies which Nye absorbed in preparing the work with particular emphasis on the clash between the Shakespearean intertexts and the diction surrounding it.